Inflammatory Profiles in Depressed Adolescents Treated with Fluoxetine: An 8-Week Follow-up Open Study - Gilberto Pérez-Sánchez; Enrique Becerril-Villanueva; Rodrigo Arreola; Gabriela Martínez-Levy; María Eugenia Hernández-Gutiérrez; Marco A. Velasco-Velásquez; Samantha Alvarez-Herrera; Carlos Cruz-Fuentes; Lino Palacios; Francisco de la Peña; Lenin Pavón (Mediators of Inflammation)
Changes in cytokine levels in major depression and during treatment have been reported in adults. However, few studies have examined cytokine levels in an adolescent sample despite this being a common age of onset. Methods. We measured proinflammatory (IL-2, IFN-γ, IL-1β, TNF-α, IL-6, IL-12, and IL-15) and anti-inflammatory (IL-4, IL-5, IL-13, IL-1Ra, and IL-10) cytokine serum levels in 22 adolescents with major depression and 18 healthy volunteers. Cytokines were measured by multiplex bead-based immunoassays at baseline, and 4 and 8 weeks after commencement of fluoxetine administration in the clinical group. Results. Compared to healthy volunteers, adolescents with major depression at baseline showed significant increases in all pro- and anti-inflammatory cytokines, except IL-1Ra and IL-10. Significant changes were observed in fluoxetine treatment compared to baseline: proinflammatory cytokines IFN-γ, IL-1β, TNF-α, IL-6, IL-12, and IL-15 were decreased only at week 4 whereas IL-2 was increased only at week 8; anti-inflammatory cytokines IL-4 and IL-5 were increased at week 8 while IL-1Ra was reduced only at week 4. There were no significant correlations between cytokine levels and symptomatic improvement in HDRS. Discussion. The results suggest a significant interplay between cytokine levels, the depressive state, and the stage of treatment with an SSRI. To the best of our knowledge, this is the first report in depressed adolescents with elevated IL-12, IL-13, and IL-15 levels. Further studies are necessary to clarify the role and mechanisms of altered cytokine levels in the pathogenesis and physiopathology of major depressive disorder.